2011
DOI: 10.1016/j.jjcc.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Elevated concentrations of pentraxin 3 are associated with coronary plaque vulnerability

Abstract: PTX3 is likely more specific than hsCRP as an indicator of coronary plaque vulnerability that could lead to plaque rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 22 publications
(21 reference statements)
2
40
0
Order By: Relevance
“…PTX3 is probably a specific indicator of coronary plaque vulnerability as assessed by the CT density of plaque [7]. As PTX3 was associated with %LV and %FV in this study, we confirmed this observation using IB-IVUS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…PTX3 is probably a specific indicator of coronary plaque vulnerability as assessed by the CT density of plaque [7]. As PTX3 was associated with %LV and %FV in this study, we confirmed this observation using IB-IVUS.…”
Section: Discussionsupporting
confidence: 86%
“…Pitavastatin also significantly reduced the elevated plasma levels of PTX3 in patients with hypercholesterolemia through its pleiotropic effect against atherosclerotic inflammation [6]. More recently, Soeki et al [7] reported that PTX3 is likely to be more specific than hsCRP as an indicator of coronary plaque vulnerability as assessed by the computed tomography (CT) density of plaques. Therefore, in this study, we confirmed that plasma levels of PTX3 are a marker for coronary plaque vulnerability as assessed by integrated backscatter intravascular ultrasound (IB-IVUS).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies, however, reported that CRP is less specific than local inflammatory markers such as pentraxin 3 as an indicator of coronary plaque vulnerability. 26, 27 In which case, we need to clarify the role of local inflammation in the production of miR-100 by using not only CRP but more specific inflammatory markers such as pentraxin 3 in further studies. .…”
Section: Discussionmentioning
confidence: 99%
“…In a study led by the authors, 31) plasma PTX3 concentrations in the coronary sinus were higher in patients with angina pectoris than in control subjects while there was no significant difference in peripheral plasma PTX3 concentrations between angina pectoris patients and control (Figure 2). These findings suggested that PTX3 was produced at the site of the coronary atherosclerotic lesion.…”
Section: )mentioning
confidence: 91%